Estimating public preferences on population health ethics - Rory Allanson; Matthew Robson (Tinbergen Institute, 2024)
We develop a social choice experiment to estimate public preferences on population ethics. Our experiment poses three within-subject treatments in which participants allocate scarce resources to determine the health-related quality-of-life, and existence, of two population groups. Within a flexible social welfare function, we estimate participant-level preferences for inequality aversion, average vs total welfare maximisation, and minimum 'critical level' thresholds. By combining random behavioural and random utility models we also explicitly model 'noise' in decision making. Using a sample of UK adults (n=115, obs.=5,060), we find that 98.7% of respondents are inequality averse, prioritising the worst-off at the expense of efficiently maximising overall health. The modal group of participants (39.2%) maximise total welfare and have a critical level threshold of zero, however there is extensive heterogeneity in participants' population preferences. We then demonstrate how these preferences can aid policymaking, where difficult trade-offs emerge between equity and efficiency, average and total welfare, and population size.
Keywords: C90; D63; I18; 330; Experiment; Health; Social Welfare; Inequality; Population Ethics